The ethylene biosynthesis genes ACS2 and ACS6 modulate disease severity of verticillium dahliae - Poulaki, Eirini G.; Tsolakidou, Maria Dimitra; Gkizi, Danai; Pantelides, Iakovos S.; Tjamos, Sotirios E. (My University, 2020)
Verticillium dahliae is one of the most destructive soilborne plant pathogens since it has a broad host range and there is no chemical disease management. Therefore, there is a need to unravel the molecular interaction between the pathogen and the host plant. For this purpose, we examined the role of 1-aminocyclopropane-1-carboxylic acid synthases (ACSs) of Arabidopsis thaliana upon V. dahliae infection. We observed that the acs2, acs6, and acs2/6 plants are partially resistant to V. dahliae, since the disease severity of the acs mutants was lower than the wild type (wt) Col-0 plants. Quantitative polymerase chain reaction analysis revealed that acs2, acs6, and acs2/6 plants had lower endophytic levels of V. dahliae than the wt. Therefore, the observed reduction of the disease severity in the acs mutants is rather associated with resistance than tolerance. It was also shown that ACS2 and ACS6 were upregulated upon V. dahliae infection in the root and the above ground tissues of the wt plants. Furthermore, the addition of 1-aminocyclopropane-1-carboxylic acid (ACC) and aminooxyacetic acid (AOA), the competitive inhibitor of ACS, in wt A. thaliana, before or after V. dahliae inoculation, revealed that both substances decreased Verticillium wilt symptoms compared to controls irrespectively of the application time. Therefore, our results suggest that the mechanism underpinning the partial resistance of acs2 and acs6 seem to be ethylene depended rather than ACC related, since the application of ACC in the wt led to decreased disease severity compared to control.
Keywords: Verticillium dahliae; Soilborne plant pathogens; Arabidopsis thaliana